Effect Of Yoga And Meditation On Stress Related Oral Ulcers Amongst Dental Undergraduates Of A Private Dental Teaching Institution In Sangareddy District - Kunusoth, Ramesh; J.D, Sunitha; Mobeen, Shaik; Dasari, Chandana; Shivani, Guggilla; Jahnavi, Ande; Khanam, Asma (Journal of Neonatal Surgery, 2025)
Background: Undergraduate dentistry students often endure significant levels of clinical and academic stress, which can lead to stress-related mouth problems, particularly recurrent aphthous ulcers. Yoga, and particularly pranayama (yogic breathing), is a well-studied non-pharmacological strategy for lowering stress and improving mental health. Objective: To investigate how undergraduate dental students' perceptions of stress and the prevalence of stress-related mouth ulcers are affected by yoga and pranayama. Methods: A cross-sectional interventional study was carried out at MNR Dental College and Hospital in Sangareddy. Two groups of 400 students each were created: Group B served as the control group and received materials, while Group A (intervention) received 15 days of supervised Pranayama training. Stress was measured using the Perceived Stress Scale (PSS-10). To find ulcers linked to stress, clinical oral examinations were performed. SPSS v25 was used to analyse the data, and chi-square and t-tests were used to assess statistical significance (p < 0.05). Clinical oral examinations were conducted to identify stress-related ulcers. Results: Prior to the intervention, 25% of students had high levels of stress, and 32.5% of students had clinical mouth ulcers. After the intervention, Group A showed a significant reduction in both high stress levels (from 25% to 2.5%) and ulcer prevalence (from 70 to 15 instances; ↓78.6%). According to chi-square analysis, there is a strong relationship between stress and mouth ulcers (χ² = 28.67, p 0.001), and yoga significantly reduces the incidence of both stress and ulcers. Conclusion: Pranayama significantly reduces the incidence of stress-related mouth ulcers and dental undergraduates' feelings of stress. Students' oral health and mental resilience may be enhanced by incorporating yoga into the dental curriculum